A Culture of Non-Judgment: Former Students’ Perspectives on the Sudbury Model Schools’ Justice System, Culture, and Relatedness - Hartkamp-Bakker, Christel A.; Martens, Rob (Critical Education, 2026)
This qualitative study explores the experiences of 14 adults who attended Sudbury model schools in the Netherlands, Israel, and the U.S. These schools emphasize student autonomy, egalitarian relationships, and minimal hierarchy. Using thematic analysis and open-ended questions, the study examines how the justice system, school culture, and staff roles supported students’ psychological needs for autonomy, competence, and relatedness, drawing on Self-Determination Theory (SDT: Deci & Ryan, 2000). Findings highlight how the justice system fostered inclusivity, mutual respect, and internalization of community norms, contributing to a culture that discouraged bullying and promoted belonging. Staff were viewed as trusted mentors rather than authority figures, reinforcing autonomy and competence. The study offers a nuanced counterpoint to critiques that SDE models reproduce neoliberal subjectivities, showing how autonomy embedded in relational safety can foster inclusion. These insights contribute to educational change debates by illustrating how non-hierarchical models can enhance student well-being and reimagine authority in schools.